1989
DOI: 10.1002/tera.1420400109
|View full text |Cite
|
Sign up to set email alerts
|

Spinal ganglia reduction in the splotch‐delayed mouse neural tube defect mutant

Abstract: Splotch and splotch-delayed mutants have anomalies in certain neural crest cell derivatives as well as neural tube defects. A genetic marker was used to identify mutant, heterozygote, and wild-type embryos within a litter, which enabled us to make intergenotypic comparisons. Histological studies of the lumbosacral region of day 15 and day 16 embryos indicated that the splotch-delayed mutant had similar but less severe defects in spinal ganglion development than those reported for splotch (Auerbach: Journal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 20 publications
4
26
0
Order By: Relevance
“…Pea3 in mutant embryos, however, was less robust than in littermate controls, suggesting that, although the mesenchyme can initiate Pea3 expression, as previously reported (Helmbacher et al, 2003), myogenic cells are required for full expression and/or maintenance of Pea3 transcripts. As expected (Moase and Trasler, 1989), DRGs were reduced in size and/or misplaced in Sp d embryos. Nevertheless, both Er81 and Pea3 were expressed in some sensory neurons in mutant embryos (Fig.…”
Section: Er81 and Pea3 Are Expressed In The Absence Of Myogenic Cellssupporting
confidence: 75%
“…Pea3 in mutant embryos, however, was less robust than in littermate controls, suggesting that, although the mesenchyme can initiate Pea3 expression, as previously reported (Helmbacher et al, 2003), myogenic cells are required for full expression and/or maintenance of Pea3 transcripts. As expected (Moase and Trasler, 1989), DRGs were reduced in size and/or misplaced in Sp d embryos. Nevertheless, both Er81 and Pea3 were expressed in some sensory neurons in mutant embryos (Fig.…”
Section: Er81 and Pea3 Are Expressed In The Absence Of Myogenic Cellssupporting
confidence: 75%
“…The peripheral nervous system in the trunk region is severely affected. In Sp heterozygotes and Sp d homozygotes, dorsal root ganglia are smaller in size and, in Sp homozygotes, they are often completely absent (Auerbach, 1954;Moase and Trasler, 1989). The defects observed in the spinal cord and peripheral nervous system of splotch mice suggests Pax-3 plays a role in spinal cord development.…”
Section: Discussionmentioning
confidence: 99%
“…Less variation is observed for spinal NTDs, spina bifida being reported to occur in 85 to 100% of homozygotes for both the Sp or Sp 2H alleles (Auerbach, 1954;Copp 1998, 2000;Gefrides et al, 2002;Martin et al, 2003), although lower rates have been reported on specific genetic backgrounds (Moase and Trasler, 1987). In some studies, occasional spina bifida is also reported in heterozygotes (Moase and Trasler, 1989;Martin et al, 2003;Li et al, 2006).…”
Section: Genetic Basis Of Neural Tube Defects In Splotch Micementioning
confidence: 99%